Quality Analysis Of Room Natural Lighting Using Spatial Interpolation With Kriging Method - Soewono, Soetjipto; Febrina Rizal, Ayu (Green Publisher Indonesia, 2022)
The results of this study, where natural lighting can affect the lighting in the room, with the entry of natural lighting into the room through 4 open windows. The data retrieval process is for 1 day through special interpolation measurements using the Kirging method. The stages of data collection are in the morning, afternoon and evening with 3 windows open and 4 windows open. The intensity of light when 3 windows are open is a minimum average of -50 lux – 1350 lux in the morning and a maximum of -50 lux -1450 lux during the day, while the condition of 4 open windows is that the minimum average lighting is 0 – 1700 lux in the morning and maximum 50 lux -1750 lux during the day d. natural lighting can make reference to the lighting schedule in the room where the condition of 4 open windows is a mix of 5 points in the afternoon and a minimum of 3 points during the day. The electric power obtained is a maximum of 36 kWh, a minimum of 21.5 kWh and the resulting cost is a maximum of RP. 51,597, a minimum of RP. 30,814.87 so that the average energy efficiency of electric power reaches 11. 75%, the highest and the lowest reaches 11. 58% and efficiency towards costs reaches 58%.